Finishing properties of plywood using shellac / Wan Mohammad Farid Wan Abdul Manaf - Wan Abdul Manaf, Wan Mohammad Farid (Faculty of Applied Sciences, 2013)
Finishing is the final process in furniture manufacturing. It is an important process that evaluates the value of the furniture product and protects wood surfaces. Often, shellac is the most popular finishing material due to its economical price and function in giving the desired appearance and providing a cleanable surface. Plywood is the most popular material that is used in wood industry that includes furniture making. wall paneling. and flooring. The purpose of this study is to determine the finishing properties of plywood using shellac with different finishing method and different number of coating layer. Surface roughness ~ hardness test, adhesion test and the household chemical test were used to determine the strength of the shellac coating into plywood. Spray finishing method has given an excellent result for the surface roughness and coating hardness. Meanwhile; brush finishing method has given an excellent result of the coating adhesion and resistance to household chemicals. However, the numbers of layer coating bas either affects on coating adhesion and the household test by using brush bas DO effects on surface roughness or coating hardness.